TREATING STRESSED PULP CONDITIONS WITH AN ENDODONTIC-RESTORATIVE DIAGNOSIS: A SYSTEMATIC REVIEW - Mohammed Alghamdi , Abdullah Alamri, Samah Alsaleem, Abdullah Aldayel, Reema Aldahshan, Adnan Bazarbashi, Nouf Alsharyan, Alaa Aldoss and Mohammed Alshehri, (Chelonian Research Foundation, 2024)
Aim: This systematic review aimed to assess the effectiveness of endodontic-restorative diagnoses in treating stressed pulp conditions and evaluate the impact of comprehensive pulp assessments on treatment outcomes. Materials and Methods: A detailed literature search was performed across multiple databases, including PubMed, the Cochrane Library, EBSCOhost, and EMBASE, to identify relevant studies addressing endodontic-restorative management of stressed pulp conditions. Ten primary studies were selected based on predefined criteria, including diagnostic approaches, treatment methodologies, and reported outcomes. Data from ten studies meeting the inclusion criteria were analyzed to determine the effectiveness of thorough pulp assessments. Results: This review revealed that comprehensive assessments of stressed pulp conditions, including detailed patient history and diagnostic testing, significantly enhanced diagnostic accuracy and treatment effectiveness. The identification of stressed pulp states is crucial for an accurate diagnosis and successful endodontic-restorative interventions. Studies have consistently shown improved outcomes when thorough evaluations are conducted before treatment. Conclusion: Incorporating detailed pulp assessments into routine clinical practice is essential for improving the efficacy of endodontic-restorative treatments. In this context, the review highlighted the need for standardized diagnostic criteria and more rigorous study designs in future research to validate these findings and advance clinical practice.